HUBUNGAN PENGGUNAAN MEDIA PEMBELAJARAN DENGAN MINAT BELAJAR SISWA DI SDN MANGKAUK 1 - Lutfiya Nurani; Inuriya Verawati; Mahrita (Yayasan Pendidikan Literasi Borneo, 2026)
This study was motivated by the low learning interest of some students, as indicated by their lack of attention, participation, enthusiasm, and engagement during the learning process. This condition is presumed to be influenced by the suboptimal use of learning media. The study aimed to identify the use of learning media, students' learning interest, and the relationship between the two at SDN Mangkauk 1. This study employed a quantitative approach with a correlational research design. The population consisted of 124 students at SDN Mangkauk 1, while the sample included 67 students from grades IV, V, and VI selected through purposive sampling. Data were collected using a Likert-scale questionnaire. The findings revealed that the use of learning media achieved a percentage of 80.24%, while students' learning interest reached 74.80%, both of which were categorized as good. The Pearson Product-Moment correlation test showed a correlation coefficient of 0.633 with a significance value of 0.000 < 0.05. These results indicate a strong and significant relationship between the use of learning media and students' learning interest. Therefore, it can be concluded that the better the use of learning media, the higher the students' learning interest at SDN Mangkauk 1.